Characterization of blackleg and soft rot from potato in northern Thailand - Athidtaya Kumvinit (2020)
© 2019 Blackwell Verlag GmbH Blackleg and soft rot of potato cause economic loss through reduced yield and quality. The causal agents of bacterial blackleg and soft rot of potato were identified based on biological data and sequence analyses of the 16S rDNA gene. Between 2016 and 2018, diseased potato stems and tubers were collected in Chai Prakan District, Chiang Mai Province, and Chiang Khum District, Pa Yao Province. The symptoms included black stem lesions, soft rot on tubers, wilting, break down of the stem vascular ring and foliar yellowing. Of 13 bacterial isolates, five were identified as Pectobacterium carotovorum subsp. brasiliense, four-Dickeya dadantii, two-Pseudomonas putida and two-Bacillus altitudinis. Pathogenicity tests of P. carotovorum subsp. brasiliense and D. dadantii resulted in lower leaves turning yellow and wilting followed by blackleg symptoms on lower stems and maceration of tuber tissue. Symptoms caused by P. putida were yellowing and wilting of leaves. B. altitudinis caused yellowing of the lower leaves and wilting followed by drying of leaf tissue. This is a first report of these bacterial pathogens causing blackleg and soft rot of potato in Thailand.